1995
DOI: 10.1007/bf00386155
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of evoked and spontaneous quantal release at high pressure in crustacean excitatory synapses

Abstract: The cellular mechanisms underlying the effect of high pressure on synaptic transmission were studied in the opener muscle of the lobster walking leg. Excitatory postsynaptic currents (EPSCs) were recorded using a loose macropatch-clamp technique at normal pressure and 3.5, 6.9 MPa helium pressure. Responses of the single excitatory axon could be grouped into two types: low-yield (L) synapses exhibiting small EPSCs with a considerable number of failures, and high-yield (H) synapses having larger EPSCs with very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Raising [Ca 2+ ] o at HP enhanced synaptic release, but its maximal effect only partially restored synaptic transmission (Grossman and Kendig, 1990; Golan and Grossman, 1992; Golan et al, 1994, 1995, 1996). Thus, synaptic release was saturated but at a subnormal level, i.e., reduced RRP (which represents the presynaptic component of the SR), and exhibited exponential FDD during stimulation at 50 Hz.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raising [Ca 2+ ] o at HP enhanced synaptic release, but its maximal effect only partially restored synaptic transmission (Grossman and Kendig, 1990; Golan and Grossman, 1992; Golan et al, 1994, 1995, 1996). Thus, synaptic release was saturated but at a subnormal level, i.e., reduced RRP (which represents the presynaptic component of the SR), and exhibited exponential FDD during stimulation at 50 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…Various lines of evidence suggest that HP impairs Ca 2+ -entry in protozoa (Otter and Salmon, 1979, 1985), brain synaptosomes (Gilman et al, 1986), and presynaptic terminals of crustacean synapses (Grossman and Kendig, 1990). Furthermore, detailed quantal analysis of crustacean neuromuscular synapses revealed that in all types of synapses HP depressed release (i.e., decreased quantal content, m ) by reducing the number of active release sites ( n ) with variable small effect on the probability of release ( p ) depending on the type of the synapses (Golan et al, 1994, 1995, 1996). Similar quantal analysis for CNS and MPP synapses are not available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1979; Grossman & Kendig, 1988), which results from a decrease in transmitter release from the presynaptic terminal (Campenot, 1975; Ashford et al . 1982; Golan et al . 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, apart from decreased slow after-hyperpolarization in hippocampal neurons (Southan & Wann, 1996) and a shift in the concentration±response curve of glycine receptors (Roberts et al, 1996), pressure does not seem to affect neuronal properties in a manner consistent with hyperexcitability (Southan & Wann, 1996;Etzion & Grossman, 1999). In contrast, a signi®cant depression of synaptic transmission is consistently demonstrated (Campenot, 1975;Wann et al, 1979;Grossman & Kendig, 1988), which results from a decrease in transmitter release from the presynaptic terminal (Campenot, 1975;Ashford et al, 1982;Golan et al, 1995). This depressant effect is attributed to a reduction of calcium in¯ux into the presynaptic terminal (Gilman et al, 1986;Grossman & Kendig, 1990;Golan & Grossman, 1992;Golan et al, 1994).…”
Section: Introductionmentioning
confidence: 99%